Experience of using ursodeoxycholic acid in the therapy of biliary sludge in children - O.Yu. Belousova; L.G. Voloshyna; O.B. Hanzii; O.M. Вabadzhanian; O.L. Slobodianiuk (Zaslavsky O.Yu., 2018)
Background. The article presents the causes, diagnostic criteria and peculiarities of pathogenetic therapy of biliary sludge (BS). The results of the study on the effectiveness of Ukrliv (ursodeoxycholic acid) are described in the correction of sludge syndrome in children. Materials and methods. Open comparative study included 60 patients with BS (42 girls, 18 boys) aged 4 months to 8 years. BS diagnosis in each child was established during ultrasound examination of the abdominal cavity. After this, two groups of 30 persons were formed by means of random sampling: study group - Ukrliv was used at a dose of 10 mg/kg body weight once a day in the evening for a month on the background of standard therapy; comparison group - children received only standard therapy. Before treatment and after it, we have evaluated clinical manifestations of the disease, the data of ultrasound examination of the abdominal cavity, the results of the biochemical study of the liver function. Results. In the study group, on the background of Ukrliv administration, BS was resolved or decreased in all children, while only 8 of the 30 children in the comparison group had spontaneous disappearance of BS. In the comparison group, the results of the biochemical study of the liver function were a little different from baseline and significantly different from indicators of the study group, where normalization of the biochemical liver functions occurred. Conclusions. Ukrliv administration contributed to the rapid resolution of BS according to ultrasound research. On the background of drug intake, there was a rapid normalization of liver function. Ukrliv did not cause side effects that would require drug withdrawal, and was well tolerated by sick children. Inclusion of Ukrliv (ursodeoxycholic acid) in the comprehensive therapy of children with BS is pathogenetically grounded.